Promoting Awareness of Emotional Development to Endorse Emotional Competence - Vidya, Bhagat; Nordin, Simbak; Kamarudin, Jaalam (2018)
Emotional development has close association in promoting emotional competency. Indeed, its implication erupts in early developmental stages through regulating, learning expressive emotional behaviour and building up relation in interpersonal domain. The purpose of the article is to promote awareness of emotional development and to endorse emotional competence. This article bases on developmental perspective of emotion and its linkage with emotional regulation trough the developmental stages and emerging competencies that upholds emotional wellbeing. In nutshell views of this article indicates that promoting emotional competency and may help in endorsing the abilities that helps to cope effectively in particular circumstances, promoting characteristics associated with positive developmental outcomes, self-efficacy, prosocial behaviour and supportive relationships in social life; it further serves as a protective factor in waning of risk factors in life.